Determining the healthy lifestyle behaviors and e-health literacy levels in adolescents - Eyimaya,Aslihan Öztürk (2021)
ABSTRACT Objective The aim of this study is to determine the healthy lifestyle behaviors and e-health literacy levels of adolescents. Method A descriptive research design was used in this study. It was conducted with a total of 390 students in the Faculty of Health Sciences. The data were collected using a personal information form, the Healthy Lifestyle Behaviors Scale II and the e-Health Literacy Scale for Adolescents. For data analysis, descriptive analyses, t-test, variance, Kruskal-Wallis, the Mann-Whitney U and Pearson Correlation tests were used. Necessary approvals were obtained to conduct this study. Results The present study found that the e-Health Literacy Scale mean score of adolescents was 27.51 and their HLBS-II mean score was 129.01. A positive significant relationship was found between the e-health literacy and healthy lifestyle behavior in adolescents. Conclusion This study emphasizes the importance of e-health literacy in developing nursing procedures designed to increase the healthy lifestyle behaviors of adolescents.